Growing Into Poverty: Reconstructing Peruvian Small-Scale Fishing Effort Between 1950 and 2018 - De la Puente, Santiago; López de la Lama, Rocío; Benavente, Selene; Sueiro, Juan Carlos; Pauly, Daniel (Frontiers in Marine Science, 2020)
Small-scale fisheries are globally marginalized by management institutions; thus, they have to endure the consequences of ineffective regulations, environmental uncertainty, social traps and market inequity. Small-scale fisheries in Peru, one of the world’s leading fishing countries, are important contributors to national employment, food security and gross domestic product. Yet, relatively little is known about these fisheries and their evolution, except for the fact that the Peruvian small-scale fleet size is rapidly increasing. Here, we developed several indicators to assess changes in the fishing efficiency and economic performance of this fleet. Segmented regression analysis was used to identify statistically significant breakpoints and changes in their trajectories between 1950–2018. Our results suggest that fishing effort has strongly increased, and at much faster rates than the catches, particularly since 2006. The combined effect of these trends results in significant declines in the fleet’s ratio indicators (i.e., catch per unit of effort, revenue per unit of effort, and fisher’s incomes relative to Peru’s minimum wage), suggesting that the growing fishing effort is unsustainable and uneconomic. The behavior of these indicators differs within the fleet, depending on the vessel’s main fishing method. Most small-scale fishers are currently living in relative poverty. Yet, fishers using the least selective fishing gears, or engaged in illegal fishing, had the most stable incomes over the past decade. These findings are discussed in detail by exploring the social, legal and economic drivers fostering fleet growth. Finally, a list of general recommendations aimed at improving fisheries sustainability and fisher’s wellbeing was produced, based on the local context, fisheries literature and common sense.